Exploring the Use of the Sustained Silent Reading (SSR) Method to Support Comprehension of Culture-Based Non-Fiction Texts Among Inclusive Students in Primary Schools: A Case Study - Aisyah, Wafa Nur; Ahmad, Mubarak (Universitas Pendidikan Indonesia, 2025)
Low literacy levels remain a significant challenge in primary education in Indonesia, particularly among students with mild Attention Deficit Hyperactivity Disorder (ADHD). This study explores the experiences of such students in applying the Sustained Silent Reading (SSR) method in third-grade primary school classrooms and describes the challenges and adjustments that occurred during the process. This qualitative case study involved three students with mild ADHD and one teacher, with data collected through observation, interviews, and documentation. Thematic analysis identified six main themes: classroom environment, adaptation of culturally based reading materials, implementation strategies of the SSR method, development of reading comprehension, challenges in maintaining focus, and the growth of self-confidence. Findings indicate that the SSR method encouraged student engagement and improved comprehension of non-fiction texts, particularly when supported by relevant materials and a conducive atmosphere. Moreover, integrating local cultural content increased students’ motivation and facilitated meaningful connections to their daily lives. The results highlight the importance of adaptive and contextualized literacy approaches in inclusive education. Overall, the study suggests that the SSR method, when modified to suit individual needs, can serve not only as a literacy strategy but also as a tool for building self-efficacy and fostering active participation among students with special needs.